2017
DOI: 10.1177/1948550617722202
|View full text |Cite
|
Sign up to set email alerts
|

Guns Automatically Prime Aggressive Thoughts, Regardless of Whether a “Good Guy” or “Bad Guy” Holds the Gun

Abstract: The mere presence of weapons can increase aggression—called the “weapons effect.” Weapons are theorized to increase aggression by priming aggressive thoughts. This research tested the robustness of the weapons effect using two large representative samples of American adults (total N = 1,097). Participants saw photos of criminals, soldiers, police in military gear, or police in regular gear with guns. Experiment 2 also included a condition with photos of Olympians with guns used to shoot inanimate targets. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…People know that Olympians use guns to shoot inanimate targets rather than people. However, when people are exposed to photos of guns that are used to shoot people, it does not matter whether the person holding the gun is a "good guy" or a "bad guy" (Bushman, 2018).…”
Section: Generalizing Beyond Violent Media Effectsmentioning
confidence: 99%
“…People know that Olympians use guns to shoot inanimate targets rather than people. However, when people are exposed to photos of guns that are used to shoot people, it does not matter whether the person holding the gun is a "good guy" or a "bad guy" (Bushman, 2018).…”
Section: Generalizing Beyond Violent Media Effectsmentioning
confidence: 99%
“…To be sure, some phenomena are manifested in strong and thus potentially more replicable effects, as has been shown by research dealing with the influence of the mere sight of individuals with a gun on subsequent aggressive thoughts (Bushman, 2018). By analogy, vigorous exercise produces stronger physiological effects than moderate and mild exercise.…”
Section: Subtle Truthmentioning
confidence: 97%
“…For example, Bartholow and colleagues (2005) showed that for hunters, the weapons effect was only present when they were exposed to assault-type firearms, but not to hunting firearms. Furthermore, Bushman (2018) showed that when the weapon is interpreted as one not intended to harm humans, that specific weapon does not prime aggressive thoughts.…”
Section: Limitations and Concernsmentioning
confidence: 99%